On the estimation of the functional - Puriuškis, Gintaras (Lietuvos matematikos rinkinys, 2007)
There is considered the functional inf(sup|f (i)(t)), The supremum is taken by i = 0, 1, 2, the infimum is taken by the function set KC2([0, 1]), with boundary conditions f (0) = 1, f’(0) = 1, f (1) = 0, f’(1) = 0.